Differences in Research Abstracts written in Arabic, French, and English - Bouziane, Abdelmajid; Metkal, Fatima Ezzahra (English Studies at NBU, 2020)
The proliferation of publications, mainly the digital ones, makes it necessary to write well-structured abstracts which help readers gauge the relevance of articles and thus attract a wider readership. This article investigates whether abstracts written in three languages, namely Arabic, French and English, follow the same patterns within or across languages. It compares 112 abstracts in the areas of (applied) linguistics. The English abstracts include 36 research article (RA) abstracts from an Arab journal mostly written by non-natives and 10 by native speakers from British universities. Those produced in French are 36 divided into two sets, 23 from North African journals and the remaining 13 from French journals. The Arabic abstracts consist of 30 abstracts, 15 from North African journals mainly from Tunisia, Algeria, and Morocco and the other 15 from the Middle East with a focus on Qatari and Saudi texts. Results emanating from the frequency of moves show that the abstracts written in English by natives and non-natives and those produced in Arabic by Middle Eastern writers show conformity with the existing conventions of abstract writing in English. However, those from North Africa, be they Arabic or French, do not share any specific patterns which can be attributed to the language in which they are written. Further research is needed to check whether abstract writing is part of the academic writing curriculum in these two latter languages.